Temperature–frequency boundary of cryogenic dynamic logic. (May 2023) - Zhuldassov, Nurzhan; Friedman, Eby G.
Abstract: Cloud computing is increasing the demand for large scale, energy efficient, and fast computing systems. A CMOS circuit style satisfying these goals is dynamic logic. Since portability is not required for cloud computing centers, these systems can support cryogenic operation. Cryogenic operation eliminates the seminal issue of dynamic circuits, loss of the logic state due to leakage currents. At higher temperatures, static logic circuits are preferable since these circuits are unaffected by leakage currents. The operating temperature therefore affects the choice of circuit style: dynamic or static. The operation of dynamic CMOS circuits at different temperatures and the temperature at which dynamic logic is preferable to static logic are discussed here. Dynamic logic operating above 1.209 GHz can be used at temperatures up to 300 K, room temperature for a 160 nm technology node. At lower frequencies, static circuits should be used. Below 77 K, liquid nitrogen temperature, dynamic logic is stable above 29.7 MHz. At temperatures below 11 K, dynamic logic circuits operating above one hertz can be used. Since dynamic logic circuits operate at DC below 4.5 K, dynamic logic is preferable at any frequency below this temperature, including liquid helium temperature, 4.2 K.